Possibility of protective role of Moringa oleifera seed oil against cadmium-induced oxidative stress (Texas Journal of Agriculture and Biological Sciences, 2023)
The research was conducted to study the extent of the preventive and curative role of crude moringa oleifera seed oil against the toxicity of cadmium that affects the functions and organs of people who are exposed to continuous and direct doses as a result of their occupation of industries dealing with cadmium as a raw material as in the manufacture of fertilizers as well as the concentrations and inhibitory dose. For moringa oleifera oil for oxidative stress resulting from the toxic dose of cadmium, the rats were divided into four groups, each group consisting of five adult mice, The first control and comparison group was injected with saline solution (0.9 ) sodium chloride, the second group was treated with (MSO) orally, with a dose of (1ml/kg) for 21 days, treated and the third group was with (cadmium) with cadmium chloride compound in saline solution at a dose of (2ml\kg (.